Curcumin Reverses Antibiotic Resistance and Downregulates Shiga Toxin Expression in Enterohemorrhagic E. coli - Martin Zermeño-Ruiz; Mirian Cobos-Vargas; Mauro Donaldo Saucedo-Plascencia; Rafael Cortés-Zárate; Leonardo Hernandez-Hernandez; Teresa Arcelia Garcia-Cobian; Teresa Estrada-Garcia; Araceli Castillo-Romero (Diseases)
Background: Enterohemorrhagic Escherichia coli (EHEC) is a considerable public health concern associated with several foodborne outbreaks of bloody diarrhea (BD) and the potentially lethal hemolytic uremic syndrome (HUS), the pathophysiology of which is attributable to the Shiga toxin (Stx) produced by this bacterium. In most patients, supportive treatment will be sufficient; however, in some cases, antibiotic treatment may be necessary. Most antibiotics are not recommended for EHEC infection treatment, particularly those that kill the bacteria, since this triggers the release of Stx in the body, inducing or worsening HUS. Azithromycin, which prevents the release of Stx and is a weaker inducer of the SOS system, has been successfully used to reduce EHEC shedding. It is necessary to identify compounds that eliminate EHEC without inducing Stx release. The use of natural compounds such as curcumin (CUR), a polyphenol derived from turmeric, has been highlighted as an alternative bactericidal treatment approach. Objective: The objective of this study was to establish the effect of CUR and its interactions with selected antibiotics on resistant EHEC O157/H7/EDL933. Methods: Bacterial cultures were exposed to CUR at three different concentrations (110, 220, and 330 µg/mL) and 1.2% DMSO, and the antimicrobial activity of CUR was assessed by measuring the optical density at 600 nm (OD600). The synergy of CUR and the antibiotics was determined with the FIC method. RT-PCR was performed to determine the expression levels of the blaCTX-M-15, catA1, acrAB-tolC stx2A, and stx2B genes. Results: Our data indicate that CUR did not affect the growth of EHEC, but when combined with the antibiotics, it acted as a bacterial resistance breaker. Synergistic combinations of CUR and cefotaxime or chloramphenicol significantly reduced colony counts. Conclusions: Our findings support the potential of CUR as a sensitizer or in combination therapy against EHEC.